Analisis Pengaruh Kompetensi Coach, Motivasi Peserta dan Kurikulum Terhadap Efektivitas Program Pendampingan Ekspor - Abdillah Sani (Lembaga Administrasi Negara, 2020)
The Results of the Implementation of the Export Assistance Program by the Indonesian Export Education and Training Center (PPEI) in 2018 in Tangerang, Bandung and Surabaya, discussed about 75 participants, of which only 32 were approved as new exporters. Although this amount is 100% of the target set, but seen from the overall participants, the achievement was only 43%. This result is not commensurate with aspects of time, effort and cost. Therefore, through this research we want to know what factors must be questioned so that this program is more effective. The 3 variables translated were trainer's competence, participant motivation and curriculum. Data collection was carried out through literature study, questionnaire collection and interviews. Data analysis uses multiple regression methods, which produce facts, and have a significant effect, with the curriculum as the variable with the strongest influence. Based on these findings, it is recommended that the curriculum be more complete, in addition to increasing the competency of trainers and participant motivation.Keywords: Export, Assistance Program, Effectiveness.